1. Religious Belief: The Contemporary Debate 2. The Gospel according to Saint Matthew, Mark, Luke, John 3. Christ in the East Syriac Tradition. A Study of the Christology of the Assyrian Church of the East and the Common Christological Declaration o - Neelamkavil, Raphael; Pudussery, Paul Savio; Kochappilly, Paulachan (Journal of Dharma, 2003)
1. William Sweet, Religious Belief: The Contemporary Debate (Dharma Endowment Lectures Series No. 6), Bangalore: Dharmaram Publications, 2003, pages vii+168, ISBN: 81-86861-57-2. 2. Michael Fallon, The Gospel according to Saint Matthew, 1997, Indian reprint, Bangalore: Asian Trading Corporation (ATC), 2002, pages 395, ISBN: 81-7086-278-7; The Gospel according to Saint Mark, 1997, Indian reprint, Bangalore: ATC, 2002, pages 293, ISBN: 81-7086-279-5; The Gospel according to Saint Luke, 1997, Indian reprint, Bangalore: ATC, 2002, pages 375, ISBN: 81-7086-280-9; The Gospel according to Saint John, 1998, Indian reprint, Bangalore: ATC, 2002, pages 386, ISBN: 81-7086-281-7. 3. George Thumpanirappel, Christ in the East Syriac Tradition. A Study of the Christology of the Assyrian Church of the East and the Common Christological Declaration of 1994, Satna: Ephrem’s Publications, 2003, pages xiii + 213, ISBN: 81-88065-02-1.